Long-life paste electrolyte and application thereof in soil buried pipeline current sensor

By using long-life paste electrolytes in soil buried pipeline current sensors, the problems of traditional electrolytes being prone to generate harmful by-products and short service life are solved, and a longer service life and lower maintenance costs are achieved, providing a more reliable guarantee for the safe operation of the pipeline.

CN119724678AInactive Publication Date: 2025-03-28LANGFANG ZHONGYIDE PETROLEUM & GAS EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028647.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrolytes in the current sensors of traditional soil buried pipelines are prone to chemical reactions, producing harmful by-products, resulting in reduced conductivity and sensor failure, and have a short service life and need to be replaced frequently, which increases the cost of system maintenance.

Method used

A long-life paste-like electrolyte is used, which consists of a silicate matrix, sulfuric acid, preservative, thickener, conductivity enhancer, pH buffer, stabilizer, antioxidant and crosslinking agent. Through the reasonable proportion and process of these components, the chemical stability and conductivity of the electrolyte are improved.

Benefits of technology

It significantly extends the service life of the sensor, reduces the replacement frequency, reduces the system maintenance cost, avoids possible damage to the pipeline during replacement, and provides more reliable technical guarantees for the safe operation of the pipeline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724678A_ABST
    Figure CN119724678A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrolytes, and discloses a long-life paste electrolyte which is prepared from the following raw materials in specific parts by weight: a silicate matrix, sulfuric acid, a preservative, a thickening agent, a conductivity enhancer, a pH buffer agent, a stabilizer, an antioxidant and the like. Wherein the silicate matrix is preferably magnesium aluminum silicate with the fineness of 200-800 meshes, the purity of the sulfuric acid is 95-98%, and the viscosity of the hydroxypropyl methyl cellulose is controlled within a certain range. The electrolyte may also include a cross-linking agent to enhance cohesion and adhesion. The preparation process comprises the following steps: mixing the matrix material, adding the liquid component, adding the thickening agent and the conductivity enhancer, adjusting the pH value, adding the stabilizer and the antioxidant, adding the cross-linking agent, heating, stirring and the like. The obtained long-life paste electrolyte has excellent chemical stability, conductivity and adhesiveness, is especially suitable for a soil buried pipeline current sensor, and can improve the service life and measurement accuracy of the sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrolytes, and specifically discloses a long-life paste electrolyte and application of the electrolyte in a soil-buried pipeline current sensor. Background Art

[0002] In the vast field of intelligent sensing systems, soil-embedded pipeline current sensors have become an indispensable key component due to their unique functions and importance. This type of sensor is buried deep in the soil and uses a precise sensing mechanism to monitor and determine whether the current in the pipeline is flowing normally in real time, providing a strong technical guarantee for the safe operation of the pipeline. Despite its small size, it plays a vital role in the entire sensing system and is the cornerstone for ensuring the stable operation of the system.

[0003] Traditionally, the electrolyte core in the sensor is mainly prepared by a mixture of pure water and sulfuric acid. This electrolyte has good conductivity and can form a stable sensing effect in the tank. Through a specific leakage design, the electrolyte forms a close electrical contact with the surrounding soil and pipeline, thereby achieving accurate sensing and measurement of pipeline current. However, as time goes by, this traditional electrolyte gradually exposes some obvious shortcomings.

[0004] The primary problem is that the mixture of pure water and sulfuric acid is prone to chemical reactions during use, generating byproducts such as copper sulfate. The accumulation of these byproducts not only affects the conductivity of the electrolyte and reduces the sensitivity of the sensor, but may also cause short circuits or corrosion in the circuits inside the sensor, leading to sensor failure. This failure not only affects the normal operation of the sensor, but may also cause a chain reaction in the entire intelligent sensing system, causing system failure.

[0005] In addition, the life of traditional electrolytes is relatively short, generally only about three years at most. In harsh soil environments, the life of the electrolyte may be even shorter. Once the electrolyte fails, the sensor replacement process will become quite difficult. Not only does it require digging the soil to remove the sensor from the ground, it may also cause certain damage to the pipes buried nearby. This replacement process is not only time-consuming and labor-intensive, but also costly, which brings great inconvenience to the maintenance and management of the system.

[0006] Therefore, in view of these problems existing in traditional electrolytes, it is urgent to develop a new type of long-life paste electrolyte to replace the mixture of pure water and sulfuric acid. This new electrolyte should have good chemical stability, be able to maintain stable conductivity during use, and avoid the generation of harmful by-products. At the same time, it should also have a long service life, which can reduce the frequency of sensor replacement and reduce the maintenance cost of the system. Summary of the invention

[0007] In view of the deficiencies of the prior art, the present invention proposes a long-life paste electrolyte and application thereof in a soil-buried pipeline current sensor.

[0008] The present invention includes the following technical solutions: A long-life paste electrolyte, which is made of the following raw materials in parts by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 20-40 parts by weight; B. sulfuric acid, as an acidic component, in an amount of 2-8 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 0.5-3 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 3-8 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, with a weight ratio of 1-5 parts; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, with a total weight of 0.5-2 parts; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 2-6 parts; H. Antioxidant, selected from vitamin E or its derivatives, used to prevent oxidation of active ingredients in the electrolyte, with a weight portion of 0.1-1 part.

[0009] Furthermore, in the above-mentioned long-life paste electrolyte, the fineness of the magnesium aluminum silicate in the silicate matrix is ​​200 mesh to 800 mesh.

[0010] Furthermore, in the above-mentioned long-life paste electrolyte, the purity of the sulfuric acid is 95% to 98%.

[0011] Furthermore, in the above-mentioned long-life paste electrolyte, the viscosity of the hydroxypropyl methylcellulose is 10000 mPa·s to 50000 mPa·s, and the viscosity is measured in a 2% aqueous solution at 25°C.

[0012] Furthermore, in the above-mentioned long-life paste electrolyte, the weight ratio of sodium dihydrogen phosphate to sodium dihydrogen phosphate in the pH buffer is 1:1 to 1:3.

[0013] Furthermore, the above-mentioned long-life paste electrolyte also includes a cross-linking agent for enhancing the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor, and the weight proportion of the cross-linking agent is 0.1-1 part.

[0014] Furthermore, in the above-mentioned long-life paste electrolyte, the cross-linking agent is di-tert-butyl peroxide DTBP.

[0015] The present invention discloses a preparation process of the long-life paste electrolyte, comprising the following steps: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

[0016] The invention also discloses the application of the long-life paste electrolyte in a soil-buried pipeline current sensor.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The long-life paste electrolyte proposed in the present invention and its application in soil-buried pipeline current sensors, by selecting a silicate matrix as the paste matrix material and adding a variety of ingredients such as preservatives, conductivity enhancers, pH buffers, stabilizers, antioxidants and cross-linking agents, effectively improves the chemical stability, conductivity, paste morphology and adhesion of the electrolyte, while enhancing its low-temperature stability and ability to prevent cracking, preventing oxidation of active ingredients, and enhancing cohesion and adhesion. This innovative design not only avoids the problem of easy generation of harmful byproducts in traditional electrolytes, but also significantly extends the service life of the sensor, reduces the replacement frequency, reduces the maintenance cost of the system, and avoids possible damage to the pipeline during the replacement process, providing a more reliable technical guarantee for the safe operation of the pipeline. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the pH value change rate in the test case; Figure 2 is the conductivity decrease rate in the test case; Figure 3 is the conductivity transverse test result in the test example; Figure 4 It is the lateral test result of adhesion in the test example. DETAILED DESCRIPTION

[0019] A long-life paste electrolyte, which is made of the following raw materials in parts by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 20-40 parts by weight; B. sulfuric acid, as an acidic component, in an amount of 2-8 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 0.5-3 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 3-8 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, with a weight ratio of 1-5 parts; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, with a total weight of 0.5-2 parts; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 2-6 parts; H. an antioxidant selected from vitamin E or its derivatives, used to prevent oxidation of the active ingredients in the electrolyte, in an amount of 0.1-1 parts by weight; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte, so that it is more firmly attached to the sensor, and the weight portion of the cross-linking agent is 0.1-1 part; The preparation method of the long-life paste electrolyte, The following steps are involved: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Embodiment 1: A long-life paste electrolyte, which is made of the following raw materials in parts by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 20 parts by weight; B. sulfuric acid, as an acidic component, 2 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight portion of 0.5 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 3 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, with a weight portion of 1 part; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, with a total weight of 0.5 parts; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight of 2 parts; H. an antioxidant selected from vitamin E or its derivatives, used to prevent oxidation of the active ingredients in the electrolyte, with a weight portion of 0.1 parts; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte, so that it is more firmly attached to the sensor, and the weight portion of the cross-linking agent is 0.1 parts; The preparation method of the long-life paste electrolyte, The following steps are involved: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

[0022] Example 2 A long-life paste electrolyte, which is made of the following raw materials in parts by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 30 parts by weight; B. sulfuric acid, as an acidic component, 4 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 1.5 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 5 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, 3 parts by weight; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, the total weight portion is 1 part; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 4 parts; H. an antioxidant selected from vitamin E or its derivatives, used to prevent oxidation of the active ingredients in the electrolyte, with a weight portion of 0.5 parts; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor, and the weight portion of the cross-linking agent is 0.5 parts; The preparation method of the long-life paste electrolyte, The following steps are involved: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

[0023] Example 3 A long-life paste electrolyte, which is made of the following raw materials in parts by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 40 parts by weight; B. sulfuric acid, as an acidic component, 8 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, 3 parts by weight; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 8 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, 5 parts by weight; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, with a total weight of 2 parts; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight of 6 parts; H. an antioxidant selected from vitamin E or its derivatives, used to prevent oxidation of the active ingredients in the electrolyte, with a weight portion of 1 part; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor, and the weight portion of the cross-linking agent is 1 part; The preparation method of the long-life paste electrolyte, The following steps are involved: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

[0024] Comparative Example 1: An electrolyte is prepared from the following raw materials by weight (similar to Example 2, but with the antioxidant and part of the thickener removed): A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 30 parts by weight; B. sulfuric acid, as an acidic component, 4 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 1.5 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight portion of 2 parts (reduced dosage); E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, 3 parts by weight; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, the total weight portion is 1 part; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 4 parts; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor, and the weight portion of the cross-linking agent is 0.5 parts; The preparation method is the same as that in Example 2.

[0025] Comparative Example 2: An electrolyte is prepared from the following raw materials by weight (similar to Example 2, but with the conductivity enhancer replaced): A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 30 parts by weight; B. sulfuric acid, as an acidic component, 4 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 1.5 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 5 parts; E. Conductivity enhancer, selected from potassium chloride (replacing sodium chloride), used to improve the conductivity of the electrolyte, 3 parts by weight; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, the total weight portion is 1 part; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 4 parts; I. A cross-linking agent, selected from di-tert-butyl peroxide DTBP, used to enhance the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor, and the weight portion of the cross-linking agent is 0.5 parts; The preparation method is the same as that in Example 2.

[0026] Comparative Example 3 An electrolyte is prepared from the following raw materials by weight (similar to Example 2, but without the cross-linking agent): A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 30 parts by weight; B. sulfuric acid, as an acidic component, 4 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 1.5 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 5 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, 3 parts by weight; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, the total weight portion is 1 part; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 4 parts; The preparation method is similar to that of Example 2, but the step of adding the cross-linking agent is omitted.

[0027] Comparative Example 4 Traditional liquid electrolytes.

[0028] Test Case 1 Oxidation stability test Sample preparation: Take appropriate amounts of the electrolyte samples prepared in the examples and comparative examples.

[0029] Environmental condition setting: All samples were placed in a test box at 50°C, 21% oxygen content, and 95% humidity for accelerated testing.

[0030] Duration: 3 months.

[0031] Color Change: Observe and record the color change of each sample.

[0032] pH value change: Use a pH meter to measure and record the pH value change of each sample and record the rate of change.

[0033] Conductivity decrease rate: Use a conductivity meter to measure and record the conductivity change of each sample, and record the decrease rate.

[0034] The results are shown in Table 1 and Figure 1 and Figure 2 .

[0035] Table 1 Oxidation stability test

[0036] It can be seen from the data in Table 1 that the electrolyte prepared by the formula of the present invention has good oxidation stability, can keep the color unchanged in an accelerated environment, and the pH and conductivity remain basically unchanged. Since the antioxidant is removed in Comparative Example 1, the electrolyte is more susceptible to oxidation during long-term use, resulting in performance degradation. The traditional liquid electrolyte (Comparative Example 4) has poor oxidation properties under accelerated conditions.

[0037] 2. Conductivity performance test Sample preparation: Take appropriate amounts of the electrolyte samples prepared in the examples and comparative examples.

[0038] Test conditions: 25°C, 50% humidity (mS / cm), results are shown in Table 2.

[0039] 3. Adhesion test Sample preparation: Take appropriate amounts of the electrolyte samples prepared in the examples and comparative examples.

[0040] Apply and place: Each sample was evenly spread on the same sensor surface.

[0041] Place it under certain environmental conditions (25°C, 50% humidity) for a period of time (24 hours) to ensure that the electrolyte is fully solidified or attached to the sensor surface.

[0042] Adhesion test: The adhesion of the electrolyte was tested using the pull-off method. (Adhesion mN) The results are shown in Table 2.

[0043] Table 2 Conductivity performance test and adhesion test.

[0044]

[0045] From the comparison of Example 2 and Comparative Example 1, due to the removal of the antioxidant, the electrolyte is more easily oxidized during long-term use, resulting in performance degradation. The amount of thickener is reduced, resulting in an unstable paste form of the electrolyte and reduced adhesion. From the comparison of Example 2 and Comparative Example 2, although potassium chloride is used as a conductivity enhancer, it also has a certain conductivity, but compared with sodium chloride, its conductivity is poor, affecting the induction and measurement accuracy of the sensor. From the comparison of Example 2 and Comparative Example 3, after removing the cross-linking agent, the cohesion and adhesion of the electrolyte are significantly reduced, and it is easy to fall off from the sensor, affecting the stability and service life of the sensor. From Examples 1-3 and Comparative Example 2, the paste electrolyte prepared by the formula of the present invention is not inferior to the traditional liquid electrolyte in conductivity, and has good adhesion.

[0046] It can be seen from the above embodiments and test examples that the long-life paste electrolyte proposed by the present invention and its application in the soil-buried pipeline current sensor, by selecting a silicate matrix as the paste matrix material and adding a variety of ingredients such as preservatives, conductivity enhancers, pH buffers, stabilizers, antioxidants and cross-linking agents, effectively improves the chemical stability, conductivity, paste morphology and adhesion of the electrolyte, while enhancing its low-temperature stability and ability to prevent cracking, preventing oxidation of the active ingredients, and enhancing cohesion and adhesion. This innovative design not only avoids the problem of easy generation of harmful byproducts in traditional electrolytes, but also significantly extends the service life of the sensor, reduces the replacement frequency, reduces the maintenance cost of the system, and avoids possible damage to the pipeline during the replacement process, providing a more reliable technical guarantee for the safe operation of the pipeline.

[0047] The above are limited to several preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A long-life paste electrolyte, characterized in that: The electrolyte is made of the following raw materials by weight: A. a paste matrix material selected from a silicate matrix, preferably magnesium aluminum silicate, in 20-40 parts by weight; B. sulfuric acid, as an acidic component, in an amount of 2-8 parts by weight; C. a preservative selected from sodium benzoate, used to enhance the chemical stability of the electrolyte, with a weight ratio of 0.5-3 parts; D. a thickener selected from hydroxypropyl methylcellulose, used to adjust the paste form of the electrolyte and improve its adhesion, with a weight ratio of 3-8 parts; E. a conductivity enhancer selected from sodium chloride, used to improve the conductivity of the electrolyte, with a weight ratio of 1-5 parts; F. pH buffer, selected from a mixture of sodium dihydrogen phosphate and disodium hydrogen phosphate, used to maintain the pH value of the electrolyte stable, with a total weight of 0.5-2 parts; G. a stabilizer selected from glycerol, used to improve the low temperature stability of the electrolyte and prevent cracking, with a weight ratio of 2-6 parts; H. Antioxidant, selected from vitamin E or its derivatives, used to prevent oxidation of active ingredients in the electrolyte, with a weight portion of 0.1-1 part.

2. The long-life paste electrolyte according to claim 1, characterized in that: The fineness of the magnesium aluminum silicate in the silicate matrix is ​​200 mesh to 800 mesh.

3. The long-life paste electrolyte according to claim 1, characterized in that: It is characterized in that The purity of the sulfuric acid is 95% to 98%.

4. The long-life paste electrolyte according to claim 1, characterized in that: The viscosity of the hydroxypropyl methylcellulose is 10000 mPa·s to 50000 mPa·s, and the viscosity is measured in a 2% aqueous solution at 25° C.

5. The long-life paste electrolyte according to claim 1, characterized in that: The weight ratio of sodium dihydrogen phosphate to sodium dihydrogen phosphate in the pH buffer is 1:1 to 1:

3.

6. The long-life paste electrolyte according to claim 1, characterized in that: The electrolyte also includes a cross-linking agent for enhancing the cohesion and adhesion of the electrolyte so that it can be more firmly attached to the sensor. The weight portion of the cross-linking agent is 0.1-1 part.

7. The long-life paste electrolyte according to claim 6, characterized in that: The crosslinking agent is di-tert-butyl peroxide (DTBP).

8. The process for preparing a long-life paste electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1 Mixing matrix materials: Put the magnesium aluminum silicate paste matrix material into a mixing container and use a stirrer at 100-300 rpm for preliminary mixing to make the matrix material evenly distributed; S2 Add liquid ingredients: While stirring at 100-300 rpm, slowly add sulfuric acid, control the addition speed to avoid excessive heat and bubbles, then add sodium benzoate preservative, and continue stirring until completely dissolved; S3 adding thickener and conductivity enhancer: add hydroxypropyl methylcellulose thickener and sodium chloride conductivity enhancer to the mixing container in sequence, and continue stirring at 100-300 rpm until a uniform paste is formed; S4 Adjust pH value: According to the required pH value, accurately weigh sodium dihydrogen phosphate and disodium hydrogen phosphate, mix them in proportion, add them to the paste, and continue stirring until the pH value is stable; S5 Adding stabilizer and antioxidant: adding glycerin stabilizer and vitamin E or its derivative antioxidant to the paste, and stirring thoroughly to make the ingredients evenly distributed; S6: adding a crosslinking agent: heating the mixture to 50-60° C., adding di-tert-butyl peroxide (DTBP) crosslinking agent to the paste, stirring the mixture rapidly at 300-600 rpm until the mixture is uniform, and cooling the mixture to room temperature to obtain the long-life paste electrolyte.

9. Use of the long-life paste electrolyte according to any one of claims 1 to 7 in a soil-buried pipeline current sensor.